2021
DOI: 10.1002/ppp.2132
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of a large, complex rock glacier and its significance in hydrological and dynamic behavior: A case study in the semi‐arid Andes of Argentina

Abstract: This paper presents an analysis of the internal structure, hydrogeology and dynamics of a large, complex, multilobate and multiroot rock glacier combining electrical resistivity tomography (ERT), hydrochemical data and differential interferometry synthetic aperture radar (DInSAR). The rock glacier consists of a series of overlapping lobes that represent different advancing stages with different degrees of conservation. The ERT surveys characterize the active layer and the upper part of the permafrost layer, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Several authors have suggested that rock glaciers, for example in the Dry Andes and the Himalaya, are hydrologically important or significant based on the potential volume of water stored in permafrost ground ice estimated using empirical approaches [24,[76][77][78][79][80][81][82][83][84][85][86][87]. Empirical estimates of ground ice volume are subject to substantial uncertainties; for example, Jones et al [76] wrote in a review of these studies that: "[ .…”
Section: Rock Glacier Hydrologymentioning
confidence: 99%
“…Several authors have suggested that rock glaciers, for example in the Dry Andes and the Himalaya, are hydrologically important or significant based on the potential volume of water stored in permafrost ground ice estimated using empirical approaches [24,[76][77][78][79][80][81][82][83][84][85][86][87]. Empirical estimates of ground ice volume are subject to substantial uncertainties; for example, Jones et al [76] wrote in a review of these studies that: "[ .…”
Section: Rock Glacier Hydrologymentioning
confidence: 99%
“…Similar flow paths have been suggested for other intact rock glaciers worldwide. Supra-permafrost flow has been observed in other mountain permafrost landforms in the Canadian Rockies (e.g., Langston et al, 2011), the Andes (e.g., Trombotto-Liaudat et al, 2020Villarroel et al, 2022) and the Alps (e.g., Rogger et al, 2017), as permafrost impedes its infiltration, evidencing a clear response in the hydrographs, even being heard when standing on it. Subpermafrost flows have been also deduced to occur in the Argentinean Andes (Trombotto-Liaudat, et al, 2020;Villarroel et al, 2022) and the Alps (Krainer and Mostler, 2002;Ikeda et al, 2008), based on indirect outcomes from hydrochemical and geodetic studies.…”
Section: Water Routing Of Ice-debris Landformsmentioning
confidence: 92%
“…Significant socioeconomic impacts are projected on human livelihoods as a result of mountainous permafrost degradation (Beniston et al, 2018;Hock et al, 2019). Perennial subsurface ice content acts as a significant fresh-water resource although the time-scales of melting and corresponding runoff contributions are still unclear (Hilbich et al, 2022;Jones et al, 2018;Villarroel et al, 2021). Rock and debris-slope instability results in increased rock-fall and debris-flow frequency and intensity, as well as landslide activity (Chiarle et al, 2021;Deline et al, 2015;Frauenfelder et al, 2018;Haeberli et al, 2017;Patton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Kenner et al, 2017;Kneisel et al, 2000;Lambiel and Pieracci, 2008;Scapozza et al, 2011), and rock glaciers (e.g. Buckel et al, 2022;Frauenfelder et al, 2008;Halla et al, 2021;Kellerer-Pirklbauer and Kaufmann, 2018;Maurer and Hauck, 2007;Villarroel et al, 2021). ERT surveys have also been applied to study bedrock permafrost on several mountains in the alps (Keuschnig et al, 2017;Krautblatter et al, 2010;Krautblatter and Hauck, 2007;Magnin et al, 2015Magnin et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation